2015
DOI: 10.1186/s40035-015-0026-0
|View full text |Cite
|
Sign up to set email alerts
|

Mini review: linkage between α-Synuclein protein and cognition

Abstract: α-synuclein is a protein that plays important roles in cognitive function in the normal brain, although its exact role is not fully understood. However, current studies reveal that defects in α-synuclein function could contribute to various neurodegenerative disorders, such as Parkinson’s disease (PD), a disease with symptomatic progression of deterioration in motor and cognitive function. Recent studies show that the level of α -synuclein in cerebrospinal fluid (CSF) is highly correlated with speed of cogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…First, ZSCAN21 is adequately expressed in this area. Second, hippocampus is an area mainly linked with the non-motor symptoms of PD, including primarily cognitive impairment and dementia that affect a high percentage of PD patients (56,57). Additionally, hippocampal accumulation of SNCA has been reported to be involved in the pathogenesis of PD and other synucleinopathies (57), suggesting that the regulation of SNCA expression in this region may be of critical importance.…”
Section: Resultsmentioning
confidence: 99%
“…First, ZSCAN21 is adequately expressed in this area. Second, hippocampus is an area mainly linked with the non-motor symptoms of PD, including primarily cognitive impairment and dementia that affect a high percentage of PD patients (56,57). Additionally, hippocampal accumulation of SNCA has been reported to be involved in the pathogenesis of PD and other synucleinopathies (57), suggesting that the regulation of SNCA expression in this region may be of critical importance.…”
Section: Resultsmentioning
confidence: 99%
“…Our primary hypothesis was that cognitive decline is associated with an abrogation of normal epoxy fatty acid status based on findings that inhibition of soluble epoxide hydrolase, an enzyme previously implicated in the regulation of microvascular tone and inflammation, protects hippocampal neuronal death and reduces cognitive decline in mice 7 , and that genetic deletion of this enzyme slows amyloid beta associated Alzheimer’s disease onset in mice 8 . Further studies have shown that sEH inhibition reduces neuroinflammation 9 and alpha-synuclein aggregation 10 , 11 , pathological feature of multiple neurocognitive disorders 12 .…”
Section: Introductionmentioning
confidence: 99%
“…SNCA ( PARK1 ) that encodes α-syn was the first gene identified to be associated with familial PD [ 34 , 35 ]. α-syn is a major component of cytoplasmic inclusions (LBs) in survived DA neurons in PD brain [ 36 , 37 ]. α-syn is highly enriched in presynaptic terminals [ 38 ].…”
Section: Introductionmentioning
confidence: 99%